2003
DOI: 10.1046/j.1538-7836.2003.00301.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma fibrin gel porosity in patients with Type I diabetes during continuous subcutaneous insulin infusion

Abstract: Summary. Background: Patients with Type 1 diabetes have a tighter plasma fibrin gel structure, to which impaired glycemic control might contribute. Improved glycemic control can be achieved with continuous subcutaneous insulin infusion (CSII). Objectives: The aim of the present study was to investigate the effect of CSII on plasma fibrin gel properties and circulating markers of inflammatory activity in patients with Type 1 diabetes. Patients and methods: Twenty-eight patients were investigated before and afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 45 publications
(77 reference statements)
0
32
0
Order By: Relevance
“…92 It is of interest that 4 to 6 months of insulin treatment with continuous subcutaneous insulin infusion in patients with longstanding type 1 diabetes led to an increase in fibrin gel porosity independent of improved glycemic control or insulin levels, but this appeared to be related to total cholesterol and plasma fibrinogen levels. 93 Other drugs used to treat diabetes have effects on fibrin structure and function. Gliclazide increases fibrin fiber thickness but reduces permeability, overall rendering the clot more susceptible to fibrinolysis.…”
Section: Glucose and Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…92 It is of interest that 4 to 6 months of insulin treatment with continuous subcutaneous insulin infusion in patients with longstanding type 1 diabetes led to an increase in fibrin gel porosity independent of improved glycemic control or insulin levels, but this appeared to be related to total cholesterol and plasma fibrinogen levels. 93 Other drugs used to treat diabetes have effects on fibrin structure and function. Gliclazide increases fibrin fiber thickness but reduces permeability, overall rendering the clot more susceptible to fibrinolysis.…”
Section: Glucose and Treatmentmentioning
confidence: 99%
“…It has been shown that total cholesterol may determine fibrin clot structure, 93 and fibrin gel porosity has been associated with lipoproteins in young patients sustaining MI. 13 It is of interest that statins appear to reduce thrombin formation and inhibit FXIII activation, reducing the formation of a stable clot.…”
Section: Lipids and Treatmentmentioning
confidence: 99%
“…Previous work has shown more compact fibrin clots in type 1 diabetic patients compared with healthy controls [7], and limited evidence suggests a thrombotic and hypofibrinolytic state in individuals with type 1 diabetes by mechanisms that are not entirely understood [8]. Manipulating glycaemia in type 1 diabetes is associated with fewer thrombotic fibrin clots but the effect on fibrinolysis has not been studied [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…53 The above findings may explain improved clot porosity after continuous subcutaneous insulin infusion, despite no improvement in HbA 1c , as this treatment is typically associated with less hypoglycemic episodes. 32 Therefore, clinical studies investigating the effects of glycemia on cardiovascular event and thrombosis risk should not only rely on HbA 1c but should take into account glucose variability and hypoglycemia, 54 which will only be possible using continuous glucose monitoring. With the development of new continuous glucose devices, a more sophisticated approach to monitoring glycemia is now a real possibility that should be explored in future cardiovascular studies in diabetes.…”
Section: Modulation Of Fibrin-related Thrombosis Risk In Diabetesmentioning
confidence: 99%
“…Initial attempts at optimizing glucose control with continuous subcutaneous insulin infusion were associated with increased plasma fibrin gel porosity, but, unexpectedly, this was not related to an improvement in glycemic control as the fall in HbA 1c was minor and nonsignificant. 32 Subsequent work from our laboratory has shown that a mean drop in HbA 1c by 13 mmol/mol is associated with a decrease in plasma clot final turbidity, indicating the formation of less compact clots. 21 Others have demonstrated that improving glycemic control in 20 subjects with type 2 diabetes has no effect on fibrinogen levels, plasma clot porosity, or turbidity curves but it results in a small reduction in clot compaction.…”
mentioning
confidence: 94%